Valorization of mullet roe by‐products for the production of polyunsaturated fatty acids rich oils. (23rd January 2023) - Kalogianni, Eleni P.; Georgiou, Despoina; Charisis, Aggelos; Exarhopoulos, Stylianos; Tzika, Paraskevi
Abstract: This work examines the potential valorization of mullet roe by‐products for the production of mullet roe oil using mild processes. Three different extraction methods with potential of scale‐up for the food industry, namely pressure (PE), supercritical fluid extraction (SFE), and solvent extraction (SE) are examined. Mild temperature conditions to prevent oil oxidation and (wherever applicable) food‐grade solvents are used. The oil yield, the composition of oils in fatty acids by GC‐FID, the level of oil oxidation (peroxide value (PV), p‐anisidine value (AV), K232 K268, TOTOX)) and the antioxidant activity (DPPH, ABTS) are determined. SE provided the highest oil recovery, followed by SFE and PE (68%, 28% and 10% respectively). The extracted oils had a high concentration of EPA and DHA and a total of 20.7%–24.3% of identified PUFAs among the fatty acids. Oxidation was the lowest in the SFE extracted oil followed by PE, PV was <2.5 meqO2, AV≤10 and TOTOX <15 in all examined oil samples. Further research is needed to optimize processing conditions for the increase in oil recovery.